Analisis Penerapan Penyajian Laporan Keuangan Berdasarkan SAK ETAP Guna Meningkatkan Nilai Relevansi: Studi Kasus Perusahaan Agrikultur Pada CV Agung Jaya - Sofro’ul Aulia Reonika; Fauziyah Fauziyah; Akhmad Naruli (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
It is very important for companies to present financial reports in order to increase the relevance value of a company. Researchers conducted research on CV. Agung Jaya. This research aims to find out how to analyze the presentation of company financial reports in accordance with SAK ETAP in order to increase relevance value. This research uses quantitative descriptive. The data sources used were obtained through documentation and interviews. The analysis techniques used are making reports on the cost of production, making profit and loss, making reports on changes in equity, financial position reports, cash flow reports and notes to financial reports. The results of this research are CV. Agung Jaya has not fully prepared financial reports in accordance with SAK ETAP. The recording carried out is not completely efficient and effective. This discrepancy is why researchers present financial reports in accordance with SAK ETAP consisting of profit and loss reports, capital changes reports, financial position reports, cash flow reports, and notes to financial reports. Having financial reports that comply with SAK ETAP can increase the relevance value, making it easier for users of financial reports to provide company information which will result in no wrong decision making.